Early Childhood Metacognitive Learning among Students of Early Childhood Teacher Education - Fadillah Fadillah (LPPM Universitas Pahlawan Tuanku Tambusai, 2020)
The purpose of this research is to describe the ability of Early Childhood Teacher Education students to carry out Early Childhood metacognitive learning.By using the developmental research method that refers to the Dick and Carey's model, the following research results are obtained: Based on the teaching of thinking, teaching for thinking and teaching about thinking, early childhood metacognitive learning is planned so that the method and media used are clear, to train students' thinking ability. The implementation of early childhood metacognitive learning is assessed from the teacher's perception, namely students of Early Childhood Education as prospective teachers and from children's perceptions. From the teacher's perception it is believed that early childhood metacognitive learning can start at the age of 2 years old. From the children's perception, early childhood metacognitive learning occurs because of the process of habituation and imitation.